2017
DOI: 10.1007/s12640-017-9730-0
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Propofol Anesthesia Changes Expression of Synaptic Plasticity Proteins and Increases Stereotypic and Anxyolitic Behavior in Adult Rats

Abstract: Propofol is a general anesthetic commonly used in pediatric clinical practices. Experimental findings demonstrate that anesthetics induce widespread apoptosis and cognitive decline in a developing brain. Although anesthesia-mediated neurotoxicity is the most prominent during intense period of synaptogenesis, the effects of an early anesthesia exposure on the synapses are not well understood. The aim of this study was to examine the effects of neonatal propofol anesthesia on the expression of key proteins that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 89 publications
1
13
0
Order By: Relevance
“…These, together with ultrastructural changes, including decreased levels of PSD 95 expression, widening synaptic cleft and hazing postsynaptic membrane as well as impaired spatial learning and memory, indicated that administration of high doses of propofol for a short time period induced long-term neurotoxicity, structural damages and functional impairments, similar to a previous observation with similar doses of propofol administered for a longer period 31. Indeed, injection with propofol affects the expression and proteolytic processing of crucial presynaptic and postsynaptic proteins, such as GAP-43 and MAP-2, in the cortex and thalamus of the developing brain in rats, which leads to permanent impairment of neuroplasticity and emotional behaviors 41. These also support the notion that healthy neurons and their intact synaptic structure are the basis of neurological function.…”
Section: Discussionsupporting
confidence: 85%
“…These, together with ultrastructural changes, including decreased levels of PSD 95 expression, widening synaptic cleft and hazing postsynaptic membrane as well as impaired spatial learning and memory, indicated that administration of high doses of propofol for a short time period induced long-term neurotoxicity, structural damages and functional impairments, similar to a previous observation with similar doses of propofol administered for a longer period 31. Indeed, injection with propofol affects the expression and proteolytic processing of crucial presynaptic and postsynaptic proteins, such as GAP-43 and MAP-2, in the cortex and thalamus of the developing brain in rats, which leads to permanent impairment of neuroplasticity and emotional behaviors 41. These also support the notion that healthy neurons and their intact synaptic structure are the basis of neurological function.…”
Section: Discussionsupporting
confidence: 85%
“…This may be explained by the short timeline of the experiment, with neurite lengths being observed within hours of anesthetic exposure, and not days afterwards to quantify lasting effects. For the impact of propofol on synaptogenesis, divergent results have been reported with regards to cell type and the age of animals 27,28 . Similarly, ketamine has been previously shown to either downregulate synaptic proteins in the hippocampus of the developing brain 29 , or to upregulate them in the cortex 30 .…”
Section: Discussionmentioning
confidence: 99%
“…However, some of them (e.g., pentobarbital, ketamine, fentanyl/droperidol) have also been reported to lead to increased mortality or be less effective in inducing anesthesia in 1–3 day old pups and can be associated with longer recovery times . Propofol has been reported to induce seizures in P4–6 rats, impair dendritic spines when GABA A receptor inhibition is still inefficient in newborns, as well as cause apoptosis, neuroinflammation, learning and memory deficits, sex‐specific neurodevelopmental deficits, and altered endocrine responses to stress …”
Section: Technical and Methodologic Issues In The Immature Rodentsmentioning
confidence: 99%